Mucormycosis diagnosed during induction chemotherapy in five pediatric patients with acute lymphoblastic leukemia. Issue 9 (27th May 2019) - Aftandilian, Catherine; Eguiguren, Lourdes; Mathew, Roshni; Messner, Anna
Abstract: Mucormycosis in pediatric oncology patients is a rare invasive fungal infection associated with significant morbidity and mortality. We describe five patients diagnosed with mucormycosis during induction chemotherapy for acute lymphoblastic leukemia at our institution. All of the patients in our series survived, some in spite of having disseminated disease. Most of the patients' chemotherapy was modified with the aim of controlling their leukemia while minimizing immunosuppression until their fungal infection was under control. Although mucormycosis is frequently fatal, rapid diagnosis and a multidisciplinary approach can lead to excellent outcomes, even in patients undergoing intensive chemotherapy.